Sick Leaves during the Low Back Pain and Influence of Obesity on its Prolonging - Dafinë Ibrahimi-Kaçuri; Vjollca Sahatçiu Meka (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Lumbar syndrome (LS) is common problem from which the patients remain bedridden, unable, therefore working productivity is lost. Stiffness (blockage) in the lumbar-sacral part of the spinal cord limits locomotors movement, flexion, extensions and other normal daily activities. Purpose of this work is to determine the duration of the sick leaves during one year period at patients with low back pain comparing with obesity. The research was carried out in the Physiatrist Service of the Institute of Occupational Medicine (IOM) during the one year period. The total number of patients included in the research was 101, who were adult employed in the Energy Corporation of Kosovo (ECK). The subjective and objective data were collected from the medical record and the duration of the sick leaves was registered. Only 11 or 10.9% of the diseased, during the period of research, didn't use their sick leaves because of the low back pain. While the greater number of them 30 or 29.7% have used one or two weeks sick leave. By the distribution of the cases according to the groups we have got similar structure, and it can be seen from the t-test, where we didn't get important statistical significance between the groups comparing to the duration of sick leaves per week (t=0.602; p>0.05). While the average number of the sick leaves of the diseased from non-obese group was 3.94 per week (SD±3.74 week), rank 0-19 week, while the result in obese group was 4.42 week (SD±3.58 week), rank 0-13 week. Sick leaves are longer at physical employees in comparison with other occupations. Psycho-social facts affect the duration of the healing.